Distributed speaker recognition using the ETSI Aurora standard - Grassi, Sara; Ansorge, Michael; Pellandini, Fausto; Farine, Pierre-André (My University, 2002)
The ETSI “Aurora” is a standard for distributed speech recognition over the mobile cellular network. We have investigated the use of the features defined in this standard for speaker recognition, in a text-independent system based on Gaussian Mixture Models (GMM). The application context is distributed speaker recognition for user authentication on the mobile cellular network. We have found that the use of the Aurora parameters would improve the performance compared with the existing alternative which is performing speaker recognition on GSM coded speech.
Keywords: ETSI Aurora; Distributed Speaker Recognition